Synthesis and crystal structure analysis of bis(benzothiazole-2-thiolato-κS)(1,10-phenanthroline-κ2N,N′)zinc(II) - Gulchekhra Abdullayeva; Batirbay Torambetov; Shakhnoza Kadirova; Shahlo Daminova (Acta Crystallographica Section E: Crystallographic Communications, 2025)
The coordination complex [Zn(C7H4NS2)2(C12H8N2)] or [Zn(MBT)2(phen)], was synthesized using ethanol solutions of Zn(CH3COO)2·2H2O, 1,10-phenanthroline (phen) and 2-mercaptobenzothiazole (MBTH-neutral). Single-crystal X-ray diffraction analysis revealed that the zinc atom resides on a crystallographic twofold axis within the asymmetric unit. In the complex, the zinc atom coordinates two 2-mercaptobenzothiazolate (MBT; anionic form of MBTH) ligands in a monodentate fashion through their sulfur atoms, while phenanthroline acts as a bidentate ligand, chelating the zinc center. Further structural analysis, including Hirshfeld surface and two-dimensional fingerprint plot studies, indicated the presence of multiple intermolecular interactions, particularly C—H...N and C—H...π interactions, contributing to the cohesion and packing of the crystal structure.